Research performance, challenges and handling approaches among academicians in health-related disciplines from a non-research Public University in Malaysia / Ai-Hong Chen - Chen, Ai-Hong (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Introduction: Research in learning institutions is a necessity due to the importance of research in knowledge and intellectual growth. However, research culture in non-research universities is comparatively still at the neophyte stage. This study investigated the research performance, challenges and handling approaches among academicians in health-related disciplines from a non-research public university. Methodology: This study was approved by the Institutional Research Ethics Committee (REC/602/19). A survey was conducted among academicians from four different health-related disciplines (medicine, health sciences, dentistry and pharmacy) in one non-research public university in Malaysia between October to December 2019. Five hundred forty-eight academicians were approached to participate in an online self-administered questionnaire. Results: The response rate was approximately 37%. On average, academicians in health-related disciplines allocated seven to eight hours per week in research activities and read about one to two journals per week. Research was mainly relied on internal (62%) and national (34%) funding. They published about 1.45 ±1.56 indexed journal per year. Time constraint, research funding, teaching overload, lack of facility, administrative burden and dealing with difficult people topped the research challenge list. An adaptive coping mechanism was preferred over a maladaptive coping mechanism. Conclusion: This study revealed positive research culture and research performance among academicians in health-related disciplines in a non-research public university. Internal driving factors and adaptive coping mechanism prevailed in dealing with research challenges. The information from the survey is useful for other non-research universities to navigate academicians in health-related disciplines amidst multiple responsibilities.